1982
DOI: 10.1111/j.1471-4159.1982.tb07966.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Deoxyuridine in Rabbit Brain

Abstract: The metabolism of [3H]deoxyuridine by rabbit brain was investigated in vitro and in vivo. In vitro, brain slices from various regions of brain and from all age groups accumulated [3H]deoxyuridine from artificial CSF. Within the slices, a portion of the accumulated [3H]deoxyuridine was metabolized to [3H]deoxyuridine phosphate, with subsequent conversion to [3H]thymidine phosphate, and ultimately [3H]DNA. The percentage of the [3H]deoxyuridine phosphorylated and subsequently converted into [3H]DNA was highest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Similarly to the purine (deoxy)nucleotides, pyrimidine (deoxy)nucleotides are synthesized in salvage reactions in the brain [87][88][89][90][91][92][93][94][95][96][97][98]. Urd and Cyd are salvaged by cytidine deaminase (CDA) and uridine-cytidine kinase (UCK) [94,97,99].…”
Section: )mentioning
confidence: 99%
“…Similarly to the purine (deoxy)nucleotides, pyrimidine (deoxy)nucleotides are synthesized in salvage reactions in the brain [87][88][89][90][91][92][93][94][95][96][97][98]. Urd and Cyd are salvaged by cytidine deaminase (CDA) and uridine-cytidine kinase (UCK) [94,97,99].…”
Section: )mentioning
confidence: 99%
“…Some of the dU in brain was converted into ( 3 H)thymidine by TS and subsequently incorporated into DNA as shown by specific methods. These and other experiments unequivocally showed that RR, TS and DHFR were present and active not only in developing but also in adult and old rabbit brains (10,11,33). In fact, 2% of the ( 3 H) in brain cortex (i.e., the tissue above the lateral ventricle) was covalently incorporated into ( 3 H)DNA in adult rabbits after the intraventricular injection of tracer ( 3 H)dU (33).…”
Section: Early Studies Of Dn Transport and Synthesis In Cns (1975y1990)mentioning
confidence: 73%
“…(There may also be ENT2 on both the apical and basal sides of the CP (22).) Therefore, it appears that the rapid clearance of tracer dT, dU and dC from rabbit CSF into blood is due, in large part, to the apically located CNT3 transport system in CP (24,32,33). Unlike the equilibrative systems that are one-half saturated at õ0.2Y0.5 mM dT, the CP system is halfsaturated at 5 to 20 mM for dN as noted above (28Y30).…”
Section: Recent Studies Of Deoxynucleoside (Dn) Transport In the Cns mentioning
confidence: 91%
See 1 more Smart Citation
“…However, our research group has identified a saturable uptake system at the BBB, which would appear to be a major pathway for the entry of thymidine into the brain (Williams & Segal, 1996). In addition, saturable transport mechanism(s) for nucleosides out of the CSF are known to exist (Spector, 1980a(Spector, , 1985Suleiman & Spector, 1982;Spector & Huntoon, 1983;Wu, Hui & Giacomini, 1993). It was thus decided to investigate the exchanges of thymidine between CSF, blood and brain in more detail using ventriculo-cisternal perfusion in the intact animal, rather than employing the isolated plexus, to determine whether the CSF could consitute a source for these deoxyribonucleosides for the brain.…”
Section: Introductionmentioning
confidence: 99%